Preparation method of few-layer MXene coated titanium composite powder
Through wet ball milling process and MXene intercalation technology, the small and pure MXene are evenly dispersed in the titanium powder, solving the problems of enhanced phase agglomeration and high impurity content, and realizing the raw material preparation of high-performance titanium-based composite materials.
Patent Information
- Application Number
- CN202311041572.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-18
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2043-08-18
AI Technical Summary
The prior art is difficult to evenly disperse few layers of pure MXene in titanium powder, resulting in enhanced phase agglomeration, high impurity content, and easy loss of functions, limiting the development of high-performance titanium-based composite materials.
Wet ball milling process combined with MXene intercalation and powder impurity removal technology, by mixing accordion-like MXene powder with titanium powder, ball milling modification in a ball milling tank, followed by screening and high-temperature vacuum reduction to remove Impurities and maintain the structural integrity of MXene.
It realizes uniform dispersion of MXene in titanium powder, has a complete structure, a small number of layers, strong binding force, low impurity content, and accurate and controllable coating content. It is suitable for the preparation of high-performance titanium-based composite materials.
Smart Images

Figure CN119489188A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of composite material powders, and specifically relates to a powder raw material preparation technology for high-performance titanium-based composite materials in the fields of powder metallurgy and 3D printing, and more specifically to a preparation method for a few-layer MXene-coated titanium composite powder. Background Art
[0002] Titanium-based composite materials use titanium or titanium alloy as the matrix. By adding one or several different reinforcing phases with excellent properties, the mechanical properties of the matrix material are improved or new functional properties are given while retaining the original metal properties, thereby meeting the urgent demand for high-performance, multifunctional titanium-based composite materials in engineering fields with more severe service conditions. For example, the ring body in the aero-engine blade disk, the fan and the high-pressure compressor and other material structural parts in aviation and military products all require titanium-based composite materials with excellent high-temperature strength, wear resistance and high thermal conductivity. At present, high-performance, multifunctional titanium-based composite materials have become irreplaceable key materials in important strategic fields such as modern aerospace, space technology, and national defense science and technology.
[0003] The type, morphology and size of the reinforcement phase are key factors that determine the performance indicators and functions of titanium-based composites. Since the development of titanium-based composites, large-sized ceramic particles and whiskers have been used as the main candidate materials for the reinforcement phase of titanium-based composites. They mainly strengthen the matrix by pinning the grain boundaries. Although they can greatly improve the strength of the titanium alloy matrix, a large amount of addition causes a significant decline in the plasticity of the material. The development of new reinforcement phases has become a research hotspot in this field. Compared with traditional reinforcement phases such as large-sized particles and whiskers, nano-two-dimensional lamellar reinforcement phases have a special strengthening mechanism in which load transfer and dislocation pile-up hindrance coexist, and it is expected to further improve the strength without significantly affecting the plasticity of the material. At the same time, two-dimensional lamellar materials usually also have special thermal and electrical conductivity functional properties, and are ideal reinforcement phases that give titanium-based composites special functional properties.
[0004] Graphene was first proposed as a nano-sized two-dimensional sheet reinforcement phase in metal-based composites and is currently the most widely used two-dimensional sheet material. However, graphene and titanium have extremely high reactivity. Whether graphene / titanium-based composites are prepared by powder metallurgy or 3D printing technology, graphene reacts to form titanium carbide after the material is formed, losing its nano-sized two-dimensional sheet structure and its special functional properties. MXene, a new type of nano-ceramic two-dimensional material developed in recent years, has many advantages such as large specific surface area, high strength and modulus, and excellent thermal and electrical conductivity. At the same time, unlike graphene, MXene, as a ceramic reinforcement phase, has high stability and reaction inertness in titanium. After powder forming parts, it is expected to retain its initial two-dimensional sheet structure and functional properties in the titanium matrix. However, the lack of production technology for high-quality MXene / titanium composite powders has become a major bottleneck restricting the development and application of MXene-enhanced titanium-based composites. Mechanical mixing is currently the main technology for preparing MXene / titanium composite powders. This involves mixing titanium powder with MAX phase powder or accordion-shaped MXene powder and dispersing them by ball milling. However, the following problems exist and high-performance titanium-based composite materials cannot be obtained: (1) MXene is prone to agglomeration in the matrix due to strong van der Waals forces, thus losing the advantages of nano-sized two-dimensional sheet materials; (2) The two-dimensional reinforcing phase MXene cannot be effectively exfoliated, and the high number of layers leads to poor performance. Although increasing the ball milling speed and time can reduce the number of MXene layers, it destroys the intrinsic structure of MXene; (3) The impurity content of the introduced MXene is high, such as O, F and other elements.
[0005] In summary, there is an urgent need to develop a composite powder preparation technology that can obtain uniform dispersion of few-layer, pure MXene in titanium powder, so as to provide important raw materials and technical support for the development of high-quality MXene / titanium composite powders for the preparation of high-performance titanium-based composite materials. Summary of the invention
[0006] The purpose of the present invention is to provide a method for preparing a few-layer, high-purity MXene-coated titanium composite powder to obtain high-quality MXene / titanium composite powder. The powder preparation method solves the problems of reinforcement phase agglomeration, high impurity content, and easy loss of reinforcement phase function in traditional mixed powders, and breaks through the technical bottleneck of introducing MXene two-dimensional lamellar reinforcement phase into titanium-based composite materials, providing an important raw material preparation technology for the development of high-performance titanium-based composite materials. The composite powder can be directly used as a powder raw material for high-performance titanium-based composite materials in the fields of powder metallurgy and 3D printing, but its application is not limited to this.
[0007] To achieve the above object, the specific technical solutions of the present invention are as follows:
[0008] A method for preparing a few-layer MXene-coated titanium composite powder, the preparation method comprising the following main steps:
[0009] The accordion-shaped MXene powder and titanium powder are mixed in proportion, and MXene-coated titanium composite powder is obtained by wet ball milling, screening and high-temperature vacuum reduction.
[0010] Specifically, the above preparation method comprises the following main steps:
[0011] 1) Put the accordion-shaped MXene powder and titanium powder into a ball mill according to the required amount of reinforcement phase, add grinding balls according to the preset ball-to-material ratio, then add the intercalation agent and ball milling solvent medium, evacuate and seal the ball mill, and then start ball milling modification according to the set parameters;
[0012] 2) After the ball milling is completed, the modified MXene-coated titanium composite powder material is screened out, and a high-temperature vacuum furnace is used for reduction treatment to remove impurities introduced during the ball milling process, and then the treated powder is vacuum-sealed and stored.
[0013] Preferably, the titanium powder in step 1) is one or more of Ti, Ti-6Al-4V alloy, Ti-10V-2Fe-3V alloy, Ti-Ni alloy, Ti-Nb-Zr-Sn alloy, Ti-Al-Sn alloy, Ti-Al-Mn alloy, and Ti-Al-Mo-V alloy, and the purity is ≥98%.
[0014] Preferably, the accordion-shaped MXene powder in step 1) is made of ternary carbides or nitrides. (n+1) AX n Phase (M represents transition metal elements, A represents main group elements, X represents carbon or nitrogen) corrosion obtained with a specific stoichiometric ratio of lamellar metal carbides, metal nitrides, composite metal carbides, such as Ti3C2, Ti3N2, Ti4N3, (Ti, Nb)4C3, Zr2C, Zr3C2, etc., any one or a combination of two or more.
[0015] Preferably, the amount of the reinforcing phase added in step 1) is the mass fraction of the accordion-shaped MXene powder in the powder mixture, ranging from 0.05 to 25.00 wt.%.
[0016] Preferably, in step 1), the ball mill and the grinding ball media are made of ceramic or stainless steel materials, such as 316L, zirconium oxide, tungsten carbide, etc.
[0017] Preferably, the intercalant in step 1) is an organic solvent that can expand the interlayer spacing of the physical phases in the accordion-shaped MXene powder and peel it into two-dimensional sheets; further preferably, the intercalant is one or more of N2H4-H2O (HM), N,N-dimethylformamide (DMF), and dimethyl sulfoxide solvent (DMSO). The intercalant can also be an organic base solution, etc. The organic base includes any one of trimethylphenylammonium hydroxide, tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrapropylammonium hydroxide, and tetrabutylammonium hydroxide solution, or a combination of two or more thereof.
[0018] Preferably, the ball milling solvent medium in step 1) is a solvent capable of dissolving the intercalant, and more preferably, the solvent is deionized water or ethanol.
[0019] Preferably, in step 1), the ball milling is performed using a planetary ball mill, and the ball milling parameters are: rotation speed range: 50 to 200 rpm; ball milling time range: 15 to 180 min.
[0020] Preferably, the high temperature impurity removal device in step 2) can be a high temperature vacuum furnace reduction device with uniform heating and cooling and low vacuum degree. The vacuum reduction parameters are temperature range: 400-800°C; reduction time: 15-180min.
[0021] The present invention provides a MXene-coated titanium-based composite powder, wherein the powder is based on titanium powder or titanium alloy powder, and the coating layer comprises MXene. Preferably, the MXene accounts for 0.05 to 20.00 wt.% of the total weight of the powder.
[0022] According to a preferred embodiment of the present invention, the present invention provides a method for preparing a few-layer MXene-coated titanium-based composite powder, comprising the following steps:
[0023] 1) Weigh a certain amount of Ti3C2 type accordion-shaped MXene powder, and then continue to weigh the corresponding proportion of titanium powder, add them into the ball mill, add zirconium oxide grinding balls according to the preset ball-to-material ratio, and then add dimethyl sulfoxide solvent (DMSO) intercalation agent and a certain amount of deionized water ball milling solvent medium, then vacuum seal the ball mill several times, and wait until the vacuum degree reaches 10 -2 After Pa, the ball milling modification was started according to the set ball milling parameters of a rotation speed of 100 rpm / min and a ball milling time of 60 min.
[0024] 2) After the ball milling is completed, the modified MXene-coated titanium-based composite powder material is screened out using a 100-mesh screen, the modified and coated powder is placed in a porcelain boat, and placed in a high-temperature vacuum furnace for high-temperature reduction and impurity removal treatment to remove impurities introduced during the ball milling process. The furnace temperature is set to 750°C, the heating rate is 10°C / min, the insulation time is 30min, and then the vacuum furnace is cooled according to the program. When the program temperature reaches 500°C, the cooling program is turned off and the furnace is cooled naturally. When the temperature drops to 50°C, the vacuum is turned off, the vacuum furnace is opened to take out the powder, and the coated powder after impurity removal is screened for different particle sizes and bagged for vacuum sealing and storage.
[0025] The present invention aims to solve the problems of poor dispersibility of MXene in composite powders, difficulty in controlling the number of layers, and high impurity content. The wet ball milling process is combined with MXene intercalation and powder impurity removal technology to achieve the goal. The prepared MXene / titanium composite powder has the advantages of complete structure, small number of layers (generally less than 10 layers), strong bonding with titanium powder matrix, etc. compared with the MXene-Ti mechanical mixed powder reported by others, the coating content is precisely controllable and the adjustable range is wide (0.05-20.00wt.%).
[0026] Compared with mechanical mixing or high-energy ball milling technology, the present invention has the advantages of not destroying the MXene structure, maintaining the original powder shape, introducing less impurities, and having a low number of MXene layers, and has good application prospects.
[0027] The surface coating layer of the present invention is mainly composed of two-dimensional MXene, and the MXene / titanium composite powder has the advantages of complete structure, small number of layers (generally less than 10 layers), strong bonding with the titanium powder matrix, etc.
[0028] Compared with the MXene / titanium composite powder prepared by traditional mechanical ball milling technology, the advantages of the present invention are:
[0029] The MXene / titanium composite powder prepared by the present invention has the advantages of complete structure, few layers (generally less than 10 layers), strong bonding with titanium powder matrix, etc., and the coating content is precisely controllable and has a wide adjustable range (0.05-20.00wt.%). The present invention is mainly achieved by wet ball milling process combined with MXene intercalation and powder impurity removal technology. Compared with traditional mechanical ball milling technology, this technology has the advantages of simple process, good coating effect, few layers (generally less than 10 layers), low impurity content, complete structure, strong bonding with titanium powder matrix, etc., good process effect, and is more conducive to being used as raw material powder in MXene enhanced titanium composite materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is a SEM image of the MXene-coated Ti hydrogenation-dehydrogenation composite powder in Example 1 of the present invention;
[0031] Figure 2 This is a high magnification SEM image of the MXene-coated Ti hydrogenation-dehydrogenation composite powder in Example 1 of the present invention;
[0032] Figure 3 This is a SEM image of the MXene-coated Ti spherical composite powder in Example 2 of the present invention;
[0033] Figure 4 This is a high magnification SEM image of the MXene-coated Ti spherical composite powder in Example 2 of the present invention;
[0034] Figure 5 This is a SEM image of the MXene-coated Ti hydrogenation-dehydrogenation composite powder in Example 3 of the present invention;
[0035] Figure 6 This is a high magnification SEM image of the MXene-coated Ti hydrogenation-dehydrogenation composite powder in Example 3 of the present invention;
[0036] Figure 7 This is a SEM image of the MXene-coated Ti-6Al-4V spherical composite powder in Example 4 of the present invention;
[0037] Figure 8 This is the SEM image of the MXene-coated Ti-6Al-4V spherical composite powder in Example 5 of the present invention. DETAILED DESCRIPTION
[0038] The technical solution of the present invention is described in detail below with reference to the accompanying drawings and embodiments.
[0039] Example 1
[0040] 1) Use weighing paper to weigh 2g of Ti3C2 type accordion-shaped MXene powder, and then continue to weigh 200g of hydrogenated dehydrogenated titanium powder, add the two successively into the ball mill, add zirconium oxide grinding balls according to the preset ball-to-material ratio of 1:1, and then add 20mL of dimethyl sulfoxide solvent (DMSO) intercalation agent and 80ml of deionized water ball milling solvent medium, then repeatedly vacuum seal the ball mill until the vacuum degree reaches 10 -2 After Pa, the ball milling modification was started according to the set ball milling parameters of a rotation speed of 100 rpm and a ball milling time of 60 min.
[0041] 2) After the ball milling is completed, the modified MXene-coated titanium-based composite powder material is screened out through a 100-mesh screen, and the modified and coated powder is placed in a porcelain boat and placed in a high-temperature vacuum furnace for high-temperature reduction and impurity removal. The furnace temperature is set to 750°C, the heating rate is 10°C / min, and the insulation time is 30min. After waiting for the insulation time to arrive, the vacuum furnace is cooled down according to the program. When the program temperature reaches 500°C, the cooling program is turned off and the temperature is naturally cooled with the furnace. When the temperature drops to 50°C, the vacuum is turned off, the vacuum furnace is opened to take out the powder, and the impurity-removed coated powder is screened for different particle sizes, and bagged for vacuum sealing and storage.
[0042] Figure 1 This is the SEM image of the MXene-coated Ti hydrogenation-dehydrogenation composite powder in Example 1. The main component of the coating layer on the powder surface is MXene, and the irregular Ti powder surface is evenly coated with MXene;
[0043] Figure 2 This is a high-magnification SEM image of the MXene-coated Ti hydrogenation-dehydrogenation composite powder in Example 1. It can be seen that the surface layer material is thinner, has fewer layers, and is no longer arranged like an accordion.
[0044] Example 2
[0045] The difference between Example 2 and Example 1 is that the hydrogenated dehydrogenated titanium powder is changed to spherical titanium powder with a particle size distribution of 25 to 53 μm.
[0046] Figure 3 This is a SEM image of the MXene-coated Ti spherical composite powder in Example 2 of the present invention, in which the rough surface of the Ti powder is coated with lamellar MXene;
[0047] Figure 4 This is a high-magnification SEM image of the MXene-coated Ti spherical composite powder in Example 2 of the present invention. MXene is evenly distributed on the spherical powder.
[0048] Example 3
[0049] The difference between Example 3 and Example 1 is that the intercalant is trimethylphenylammonium hydroxide solvent.
[0050] Figure 5 This is a SEM image of the MXene-coated Ti hydrogenation-dehydrogenation composite powder in Example 3 of the present invention;
[0051] Figure 6 This is a high-magnification SEM image of the MXene-coated Ti hydrogenation-dehydrogenation composite powder in Example 3 of the present invention.
[0052] Example 4
[0053] The difference between Example 4 and Example 2 is that the spherical titanium powder is replaced with spherical Ti-6Al-4V powder, the powder purity is 99.0%, the particle size distribution is 25-53 μm, and the ball mill rotation speed is 200 rpm.
[0054] Figure 7 This is the SEM image of the MXene-coated Ti-6Al-4V spherical composite powder in Example 4 of the present invention. A few layers of MXene are still evenly coated on the powder surface, confirming that the MXene coating method has no obvious selectivity for the titanium alloy powder matrix.
[0055] Example 5
[0056] The difference between Example 5 and Example 4 is that the ball milling parameters are set to a rotation speed of 200 rpm / min and a ball milling time of 180 min.
[0057] Figure 8 This is the SEM image of the MXene-coated Ti-6Al-4V spherical composite powder in Example 5 of the present invention. The results show that by increasing the ball milling speed, the MXene can be distributed more evenly, but there is also the risk of decomposing the MXene into multiple smaller nanosheet layers.
[0058] The process parameters (such as temperature, time, etc.) of the present invention can realize the method by taking upper and lower limits and interval values, and the embodiments are not listed one by one here.
[0059] Any contents not described in detail in the present invention can be based on the conventional technical knowledge in the art.
[0060] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the present invention. Although the present invention is described in detail with reference to the embodiments, it should be understood by those skilled in the art that any modification or equivalent replacement of the technical solutions of the present invention does not depart from the spirit and scope of the technical solutions of the present invention and should be included in the scope of the claims of the present invention.
Claims
1. A method for preparing a few-layer MXene-coated titanium composite powder, the preparation method comprising the following main steps: The accordion-shaped MXene powder and titanium powder are mixed in proportion, and MXene-coated titanium composite powder is obtained by wet ball milling, screening and high-temperature vacuum reduction.
2. The preparation method according to claim 1, characterized in that: The titanium powder is one or more of Ti, Ti-6Al-4V alloy, Ti-10V-2Fe-3V alloy, Ti-Ni alloy, Ti-Nb-Zr-Sn alloy, Ti-Al-Sn alloy, Ti-Al-Mn alloy, and Ti-Al-Mo-V alloy, and the purity is ≥98%.
3. The preparation method according to claim 1, characterized in that: The few-layer MXene-coated titanium composite powder refers to a coating layer number of ≤10.
4. The preparation method according to claim 1, characterized in that: The accordion-shaped MXene powder is Ti3C2, Ti3N2, Ti4N3, (Ti,Nb)4C3, Zr2C or Zr3C2.
5. The preparation method according to claim 1, characterized in that: The mass fraction of the accordion-shaped MXene powder in the powder mixture is 0.05 to 25.00 wt.%.
6. The preparation method according to claim 1, characterized in that: The medium of the ball milling jar and the grinding balls used in the wet ball milling is ceramic or stainless steel.
7. The preparation method according to claim 1, characterized in that: An intercalant is added during the wet ball milling process, and the intercalant is one or more of N2H4-H2O, N,N-dimethylformamide, dimethyl sulfoxide, trimethylphenylammonium hydroxide solution, tetramethylammonium hydroxide solution, tetraethylammonium hydroxide solution, tetrapropylammonium hydroxide solution and tetrabutylammonium hydroxide solution.
8. The preparation method according to claim 1, characterized in that: During the wet ball milling process, a ball milling solvent medium is added, and the ball milling solvent medium is deionized water or ethanol.
9. The preparation method according to claim 1, characterized in that: The wet ball milling adopts a planetary ball mill, the ball milling speed is 50-200 rpm, and the ball milling time is 15-180 min.
10. The preparation method according to claim 1, characterized in that: The temperature of the high-temperature vacuum reduction is 400-800° C. and the reduction time is 15-180 minutes.
Citation Information
Patent Citations
Method for preparing granular titanium dioxide / two-dimensional nano-titanium carbide composite material
CN104495918A
Titanium carbide in-situ-growth CNTs three-dimensional composite material with carbon microspheres being transition layers and preparing method thereof
CN106784706A
Preparation method of two-dimensional layered MXene nanosheet
CN108298541A
Single-layer MXene nanosheets and preparation method thereof
CN111591992A
Novel catalytic material MXene / ZnMnO3 and preparation method thereof
CN115275224A